Evolving Wage Cyclicality in Latin America - Gambeti, Luca (Published by Oxford University Press on behalf of the World Bank, 2020)
This paper examines the evolution of the cyclicality of real wages and employment in four Latin American economies, Brazil, Chile, Colombia, and Mexico, during the period 1980–2010.Wages were highly procyclical during the 1980s and early 1990s, a period characterized by high inflation. As inflation declined wages became less procyclical, a feature that is consistent with emerging downward wage rigidities in a low inflation environment. Compositional effects associated with changes in labor participation along the business cycle appear to matter less for estimates of wage cyclicality than in developed economies.